Factors influencing single-bicycle crashes at skewed railroad grade crossings. (December 2017) - Ling, Ziwen; Cherry, Christopher R.; Dhakal, Nirbesh
Abstract: Cycling as a healthy and environmental friendly transport mode is gaining popularity. Most research on cyclist safety is focused on crashes involving light vehicles, trucks, or pedestrians. Only a few studies address single-bicycle crashes, and fewer focus on bicycle crashes at skewed railroad grade crossing. This study relies on empirical video data collected from a heavily travelled railroad grade crossing over a two month period, covering more than 2000 bicycle traversings and 32 single-bicycle crashes caused by tire interaction with the rail flangeway. A representative random sample of 100 successful traversings were drawn from the population and analyzed against the crashes. Video data was mined to identify crash factors, including demographic, riding behavior, bicycle characteristics, and environmental characteristics. A binary logistic regression model was built to explore factors that influence bicycle crashes. Approach angle is the most significant determinant of crashes, with a critical traversing angle of 30°. Group riders, women, and wet roadway conditions all contribute to higher odds of a crash. Crash rates are dramatically reduced at approach angles greater than 30°, and (in our dataset), non-existent at angles greater than 60°. Road-railway crossing should be designed with increased scrutiny. We suggest countermeasures, like jughandle designs, that improve the approach angle for cyclists. This study focuses on bicycle crash at railway crossings using empirical data. It fills up the gap in the research on this type of crashes and addresses issues on potential bicycle facility design at railway crossings. Highlights: Used video to monitor and collect data on single-bicycle crashes at rail crossings. Estimated binary logistic regression model of factors influencing crash outcome. Crash rate dramatically reduced when crossing angle >30°, eliminated >60°. Crash rates higher for women, road bikes, while braking, in groups, and wet surface. Bike lane realignment (e.g., jughandle) or flangeway fillers could reduce crashes.